P065 REDD1/autophagy-driven NETosis promotes IL-1β-mediated inflammation in active ulcerative colitis. (16th January 2018) - Chrysanthopoulou, A; Angelidou, I; Mitsios, A; Arelaki, S; Arampatzioglou, A; Kambas, K; Ritis, D; Tsironidou, V; Moschos, I; Mitroulis, I; Kouklakis, G; Skendros, P
Abstract: Background: Neutrophil extracellular traps (NETs/NETosis), formed by activated neutrophils upon certain inflammatory stimuli, mediate the release of a variety of proteins which are related with distinct phenotypes of neutrophil-driven disorders. In this context, IL-1β-bearing NETs are correlated with inflammatory flares of common autoinflammatory diseases. Even though the presence of NETs has been described in colonic biopsies of patients with ulcerative colitis (UC), the mechanism that orchestrates their formation and their effect on mucosal inflammation have not been clarified yet. Methods: Colonic tissue biopsies, sera and peripheral blood neutrophils collected from treatment-naive and mesalazine-treated active UC patients ( n = 15–8), treatment-naive active Crohn's disease (CD) patients ( n = 11), patients suffering from infectious enterocolitis (IC, n = 15) or healthy individuals (controls) ( n = 25). NET formation and NET-related proteins were studied using immunofluorescence, ELISA assays, immunoblotting, flow cytometry and qPCR. Furthermore, in vitro cell and tissue culture systems were performed. Results: The intestinal inflammatory environment of active UC, in contrast to CD, induces ex vivo and in vitro neutrophil activation, IL-1β expression and NETs release, both in colonic and peripheral neutrophils, mechanistically explaining intestinal and systemic manifestations. Additionally, mucosal environment of active UC is able to up-regulate the component of hypoxia and stress response REDD1 in colonic tissue neutrophils. REDD1 is correlated with the induction of autophagy, leading to formation of inflammatory NETs bearing bioactive IL-1β. This phenomenon is reduced proportionally to the distance from the inflamed area of colon, suggesting that REDD1 expression in colonic neutrophils is involved and closely related with the degree of intestinal inflammation. Expression of REDD1 and IL-1β in inflamed colonic tissue and peripheral blood neutrophils, respectively enable the distinction of active UC from CD and IC. Moreover, IL-1R antagonist, anakinra, was effective against sacroiliitis attacks in two refractory cases of UC and mesalazine significantly reduced the ex vivo and in vitro production of IL-1β in neutrophils of patients with UC. Conclusions: This study provides a novel mechanistic basis for active UC that supports the autoinflammatory nature of the disease. REDD1/neutrophils/IL-1β axis emerges as a key player in intestinal and systemic inflammation of UC providing candidate targets for novel therapeutic and diagnostic approaches.